O papel dos valores na ciência : Thomas Kuhn e Hugh Lacey - Lopes, Bruno Iauch (2014)
This study outlines the approach to science through values in Thomas Kuhn and Hugh Lacey. The exposition begins with the separation between factual judgment and value judgment as shown by the Vienna Circle. It presents the proposal for a historiography of science in Thomas Kuhn and his descriptive perspective of science as guided by values and not purely objective criteria. It shows the use that Hugh Lacey makes of the approach through the values in relation to theories of neutrality and impartiality of science and presents his proposal on separation of the analysis of science at different logical moments. As the outcome of the presentation we have that the approach to science through the values, as developed in the works of Kuhn and Lacey, exibits greater explanatory and normative power than the recourse to the dichotomy judgment of fact / value judgment.